Vandalism is a manifestation of an aggressive behavior - Карина Анатоліївна Бочарова (Проблеми Законності, 2016)
A lot of deviant behavior manifestations regarding cultural, historical, social and educational objects of property valuable for the population and state appeared on the territory of the modern urban areas. It should be taken into account that the demonstrations of aggression and a deviant behavior constitute a system of acts committed by an individual or by some destructive groups that deviate from the generally accepted rules. At the same time, every act of an individual is a conscious action, act of self- determination, where a person affirms himself/herself as a personality in relations to another person, to himself/herself, social groups or society. In recent years, violence and cruelty among the population and destructive behavior of young people and teenagers arose consequently the number of vandalism acts increased.